CoSn(OH) 6 nanocubes as a solid sorbent for the effective preconcentration of copper ions in cinnamon ( Cinnamomum zeylanicum ) extract - Bahcivan, Aleyna; Saylan, Meltem; Sagdic, Osman; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2024)
This study was aimed at developing a simple and efficient CoSn(OH) 6 nanocubes-based preconcentration method for the preconcentration of copper ions from cinnamon extracts for determination by flame atomic absorption spectrometry. The cube -shaped sorbent was synthesized using the simple stoichiometric co -precipitation method under ambient conditions. Experimental factors of the method were evaluated with a comprehensive optimization approach to maximize the extraction efficiency for the analyte. Under the optimal conditions, the limit of detection (LOD), limit of quantitation (LOQ), and linear dynamic range were recorded as 0.98 mu g/L, 3.28 mu g/L, and 4.0 -75 mu g/L, respectively. The enhancement factor was calculated as 101.6 -fold by comparing the LODs of the optimized and direct analysis systems. Percent recoveries were found to be within an acceptable range (77.6 -115 %), with high repeatability using matrix matching calibration strategy. Results validated the proposed method as a highly efficient extraction approach for the monitoring of copper ions in herbal cinnamon extracts.
Keywords: Copper; Cube-shaped nanomaterial; Flame atomic absorption spectrometry; Herbal extract; Matrix matching calibration; PHASE EXTRACTION; WATER; MANGANESE(II); SPECTROSCOPY; ADSORPTION; SEPARATION; METALS; CD(II); NICKEL; CU(II); Chemistry; Food Science & Technology; Nutrition & Dietetics